Prospective longitudinal study of biochemical changes in critically ill patients with severe traumatic brain injury: Factors associated and outcome at 6 months - Dhandapani, SS; Manju, D; Vivekanandhan, S; Agarwal, M; Mahapatra, AK (Indian Journal of Neurotrauma, 2010)
Biochemical prognostic markers of severe traumatic brain injury have not been clearly identified. This study was conducted to study biochemical changes in patients with severe traumatic brain injury, with respect to neurological outcome.Adult patients admitted within 24 hours of traumatic brain injury with Glasgow Coma Score 4-8, were prospectively studied for changes in various biochemical parameters. Outcome was assessed at 6 months. The mean serum albumin levels showed progressive fall till 2 weeks from 3.23 g/dL to nadir value of 2.86 g/dL, followed by mild increase to 2.99 g/dL at 3 weeks (p<0.001). The mean daily urine creatinine values demonstrated significant fall from 1255.4 mg/d to 1010.2 mg/d at 3 weeks (p<0.001). There was significant increase in mortality at 2 months among patients with atleast 15% fall in serum albumin and urine creatinine less than 1000 mg/d at 3 weeks (p < 0.005). Unfavorable outcome was noted in 12 out of 15, with at least 15% fall in serum albumin at 3 weeks, compared to 11 out of 25, with less than 15% fall in serum albumin (p=0.03). Unfavorable outcome was also noted in 16 out of 22, with low urine creatinine (<1000 mg/d) at 3 weeks, compared to 6 out of 17, with normal urine creatinine (p=0.02).In patients with severe TBI, unfavorable neurological outcome at 6 months was associated with 15% fall of serum albumin or low urinary creatinine at 3 weeks, more so with the former.
Keywords: biochemical changes; factors; outcome; traumatic brain injury